The role of non-profit organizations : an economic analysis - Vajčner, David (2015)
This thesis investigates the economic theories on the role on non-profit organizations, their creation, and factors for the size of the non-profit sector. An analytical approach was taken to determine what factors seem to affect the size of the non-profit sector. Firstly a literature review was conducted of the existing, and predominant economic theories relating to the role of the non-profit sector, and several hypotheses where suggested from the analysis of past research. Then an empirical model was created to test the validity of the hypotheses on a cross-national sample, in an effort to deduce what factors affect the size of the non-profit sector.